Chapter Another Sicily, tuna-fishing structures and landscape: a diachronic and contemporary photographic journey along the Sicilian western coast - FONTANA, MAURO (Proceedings e report, 2020)
The research investigates the Sicilian western coast contemporary landscapes starting with an historical study about tonnare, architectural heritage and physical expression of the tuna-fishing's tradition. The aim is to demonstrate that the Sicilian coastal landscape has undergone changes whose meaning is to be investigated to recover the coast ualities for the purposes of targeted actions of preservation and enhancement of architectural and landscape heritage. The research includes a diachronic photographic comparison between a reportage taken in 1986-1987 and photos taken in 2018.